UJI EFEKTIVITAS PUPUK PETROKALIMAS TERHADAP PRODUKSI KENTANG DI KLEDUNG KABUPATEN TEMANGGUNG - Endang Iriani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Potato (Solanum tuberosum L.) is one of the important vegetable crops in Indonesia. Potato production has grown rapidly over the past decade, and now Indonesia has become the largest potato producing country in Southeast Asia. This commodity is a commodity to be developed given the potential prospective market absorption continues to increase. According to data from the 2009 level of consumption of vegetables magnitude 37.94 kg / capita / year. The use of artificial fertilizers to increase crop yields but reduce the negative impacts of soil fertility. To overcome this needed technology that could save the use of agrochemicals to maintain soil fertility, improve product quality, and increase farmers' income. Fertilizing is an effort to maintain and preserve the balance of nutrients in soil solution through the input of nutrients from fertilizers, to support the potato crop production optimization. Effectiveness and efficiency of fertilization was influenced by the type of fertilizer, how, time, dose, and frequency of application. The purpose of the assessment to determine the effectiveness of fertilizer dosage Petrokalimas on growth and yield potato. So the expected output is data and information level of effectiveness Kalimas fertilizer on potatoes, which can ultimately balanced fertilization technology available information on the use of fertilizers Kalimas potatoes. Testing the use of fertilizer on potato Petrokalimas held in the village Kledung, Kledung District, County Waterford, which is planted in mid March 2008 and harvested in mid-June 2008. Research in the design using a randomized block design (RAK), each treatment was repeated 3 times. In this study, comparing several dosages of Petrokalimas (3 kinds of doses), the standard fertilizer, and control (fertilizer with a custom farmer). The parameters observed included agronomic data and economic analysis. The assessment indicated that availability of P2O5 and K2O on the location of the study is high, but low N availability. In potato plants, the use of fertilizers as a source of K2O Kalimas Petro results are not significantly different from that recommended the use of KCl. Increased use of fertilizer on crop Potato Petro Kalimas than 300 kg / ha up to a dose of 500 kg / ha, the value of R / C increase correlated positively with fertilizer pningkatan Kalimas Petro. Results of financial analysis on the most profitable potato crop is the use of fertilizer 200 kg / ha Urea + 500 kg / ha ZA + 300 kg / ha SP36 + 200 kg / ha ZK Petro Kalimas with the R / C ratio of 2.25